The Clash of Islam and Christianity in the Thought of Martin Luther in the Age(XVI) - Muhammad , Nahro Ismael (Zanco Journal of Human Sciences, 2021)
The clash of religions and the logic of managing conflicts and wars was mostly the logic prevalent in the Western world within their ideological and religious trends throughout the ages. Logic on its foundations they used to present their assessment of conflicts and wars. Also, the clash of religions came against the background of the economic struggles of the nations. Martin Luther believes that Islamic civilization poses a new challenge to the Christian world. For reasons related to the fundamental differences in terms of language, culture and religion. This challenge appeared at a time when Luther wanted to cleanse the Christian world of all impurities and ideas that are not compatible with his reform path, although he was able to create change. Radically and comprehensively in the Christian religion, in its foundations and prevailing rituals, through his new propositions and ideas, which differed from his predecessors, but he did not deviate from hostility to other religions, Judaism and Islam. And on Luther's religious reforms, which fully reflected on his actions and positions, as he viewed Islam in a negative light and described it as the destructive opponent of the West and the Christian world because Islam makes the identity religion the nation allowance and increases the differences. Likewise, the relations of the Islamic world adjacent to the borders of the Western world by land and sea along the Mediterranean Sea and for several eras were dominated by conflicts and wars, such as the Crusades and the wars of Morocco and Andalusia until the emergence of the Ottoman Turks and their expansion towards the West. From this standpoint, Luther tried to explain and clarify the religious belief of the Turks, so that the Germans and the Christian world would be warned of the dangers of that doctrine called (Muhammadiyah).